2016
DOI: 10.1080/15389588.2015.1109082
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for the severity of injury incurred in crashes involving on-duty police cars

Abstract: Police cars are exempted from certain traffic laws under emergency circumstances. However, to reduce the probability of being involved in a crash resulting in severe injuries, officers are still obligated to drive safely and follow safety procedures when responding to emergencies or pursuing a car. Enhancement of training techniques for emergency situations or driving in pursuit of an offender and following the safety procedures are essential for safety in driving during an emergency run by police.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 60 publications
1
15
0
Order By: Relevance
“…Particularly, driver characteristics have been extensively considered as an important risk factor influencing road traffic accident injury severity, while the association between drivers' or other vulnerable users' age group and injury severity was highly addressed. Other most recent studies (Chu, 2015;Curry et al, 2014;Lee and Li, 2014;Ma et al, 2015;Martensen and Dupont, 2013;Weiss et al, 2014) highlighted the association between younger drivers and an injury severity increase. found that younger and mid-age drivers were less likely to be involved in more severe injuries.…”
Section: Earlier Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…Particularly, driver characteristics have been extensively considered as an important risk factor influencing road traffic accident injury severity, while the association between drivers' or other vulnerable users' age group and injury severity was highly addressed. Other most recent studies (Chu, 2015;Curry et al, 2014;Lee and Li, 2014;Ma et al, 2015;Martensen and Dupont, 2013;Weiss et al, 2014) highlighted the association between younger drivers and an injury severity increase. found that younger and mid-age drivers were less likely to be involved in more severe injuries.…”
Section: Earlier Studiesmentioning
confidence: 99%
“…Many earlier research (Chu, 2015;Chung et al, 2014;Hao and Daniel, 2014;Kim et al, 2008;Kröyer, 2015;Ma et al, 2015;Mitchell et al, 2015;Sasidharan et al, 2015) exhibited driver's violation of speed limits were extensively associated with increasing more severe injuries. The results of another earlier research revealed that speed control might have a significant impact on decreasing more severe injuries.…”
Section: Earlier Studiesmentioning
confidence: 99%
See 3 more Smart Citations